2006
DOI: 10.1039/b511625m
|View full text |Cite
|
Sign up to set email alerts
|

A trinuclear Pt(ii) compound with short Pt–Pt–Pt contacts. An analysis of the influence of π–π stacking interactions on the strength and length of the Pt–Pt bond

Abstract: In this work we report the first example of a trinuclear Pt(II) complex with Pt-Pt-Pt bonds that are not facilitated by direct intervention of bridging ligands but are partially held by the attractive pi-pi stacking interaction between the phenyl units of the 4,4'-dimethyl-2,2'-bipyridyl ligands. The effect of the pi-pi stacking interactions on the strength and length of the Pt-Pt bond has been discussed using reduced models of the interacting moieties in which the aromatic rings have been removed. The nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 78 publications
5
40
0
Order By: Relevance
“…(1-a) from the crystallographic data, resulting in a perfect agreement between the DFT structure and the X-ray structure (rmsd = 0.046 Å for distances and 1.38 for angles) 1 [106][107][108][109][110][111][112], validating the computational method [62]. (1-a) from the crystallographic data, resulting in a perfect agreement between the DFT structure and the X-ray structure (rmsd = 0.046 Å for distances and 1.38 for angles) 1 [106][107][108][109][110][111][112], validating the computational method [62].…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…(1-a) from the crystallographic data, resulting in a perfect agreement between the DFT structure and the X-ray structure (rmsd = 0.046 Å for distances and 1.38 for angles) 1 [106][107][108][109][110][111][112], validating the computational method [62]. (1-a) from the crystallographic data, resulting in a perfect agreement between the DFT structure and the X-ray structure (rmsd = 0.046 Å for distances and 1.38 for angles) 1 [106][107][108][109][110][111][112], validating the computational method [62].…”
Section: Resultsmentioning
confidence: 92%
“…As a benchmark system, we have used the adsorption of acetaldehyde on rutile TiO 2 (110) surface. From a natural population analysis, it is found that the calculated charges of the Si atoms are almost independent of the type of carbon atom to which they are bonded but the charges on the neutral silicate fragments are less positive and the charges on the anionic silicate fragments are more negative when compared with those in the pure silicates, either the neutral SN2 or the singly deprotonated SNSI species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts show that the oxygen donor atom has slightly compressed the Rh-Rh bond distance in 0.065Å, which is 0.025Å less than in the Rh-N core. Furthermore, a strong -stacking interaction was found in compound 4 with a distance of 3.403Å among the coumarin rings ( Figure 7(b)) [71][72][73][74][75]. It is possible that the natural bulkiness of either methyl or isopropyl groups in the complexes 1-2 was clearly enough to affect the unit cell packing with a concurrent missing of the -stacking interaction.…”
Section: X-ray Structural Analysis Of Complexes 1-2 Andmentioning
confidence: 99%
“…In particular, Schleyer et al introduced the nucleus-independent chemical shift (NICS) as a convenient magnetic criterion for aromaticity in 1996 [20], the scope of aromatic research achieves a further development [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Recently, M. Solà and coworkers reported many important research results connected with the concept of aromaticity [35][36][37][38][39][40][41][42]. Very recently, they investigated three in-plane and three out-ofplane deformations on the aromaticity of the benzene molecule, and found that only the aromatic fluctuation index (FLU) is able to indicate the expected loss of aromaticity because of distortion from the equilibrium geometry in all analyzed deformations [43].…”
Section: Introductionmentioning
confidence: 99%